The Influence of the Terrain on the Monsoon Climate in Kathmandu and Darjeeling Regions of the Himalayas - Kiesewetter, Will (Himalayan Review, 2011)
Not available. Key words: Monsoon; Climate; Kathmandu; Darjeeling The Himalayan Review Vol. 12, 1980 Page: 53-81 Uploaded Date: April 5, 2011